(untitled) (Pathibhara Journal of Multidisciplinary Research, 2026)
Nepal is highly vulnerable to natural disasters due to its geographic structure. It has been receiving significant aid to respond to the disaster’s relief, reconstruction, and rehabilitation. Nepal Red Cross Society (NRCS) is the primary international aid recipient. This study employs a qualitative case study methodology, focusing primarily on the Nepal Red Cross Society (NRCS) and its corruption scandal that emerged after the 2015 Nepal earthquake. It is solely conducted by desk research for comprehensive secondary data such as literature, inquiry reports, media coverage, and official documents related to the NRCS. To understand financial anomalies and their origins, the study scans multiple sources. The objective of this study is to link NRCS wrongdoing to humanitarian aid misuse. After the 2015 earthquake, several NGOs, including the NRCS, engaged in such a chaotic competition for humanitarian support. Among them, the NRCS benefited most from these payments. Multiple government authorities found evidence of nearly RS 16 billion in foreign aid misappropriation by the NRCS. The study indicates that NRCS implemented 98 different projects costing Rs 5.044 billion without obtaining prior approval from the Social Welfare Council (SWC). According to the identified reports, NRCS spent 15 billion, 61 million, 18 million, seven thousand, three hundred, and 74 rupees. The latest recorded data shows total recoverable amounting to Rs 19.41 m have not been recorded in the NRCS accounts. Likewise, outstanding rent fees amounting to Rs 20.19m from various individuals and firms have not been collected, with some pending since the fiscal year 2020/ 21. The findings indicate that NRCS exhibits a deficiency in integrity and does not uphold anti-corruption compliance. Transparency and accountability are essential for the ethical and effective utilization of international aid. This research highlights NRCS’s urgent need for compliance, maintenance, and re-establishing trust as a humanitarian recipient organization.